2014
DOI: 10.1016/j.orgel.2014.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating backbone structure with various conjugated spacers to enhance photovoltaic performance of D–A-type two-dimensional copolymers

Abstract: a b s t r a c tA class of low band-gap two-dimensional conjugated polymers of PBDTT-FQ, PBDTT-TQ, PBDTT-BTQ and PBDTT-TTQ was designed and synthesized, which contains the same di(alkylthiophene)-substituted benzo [1,2-b:4,5-b 0 ]dithiophene (BDTT) and 6,7-difluoroquinoxaline (Q) units, as well as various conjugated spacers of furan, thiophene, bithiophene and thieno [3,2-b]thiophene in the main chain. Significant effect of the varied spacers between the BDTT and Q units on the thermal, optical, electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 47 publications
(49 reference statements)
0
20
0
Order By: Relevance
“…29 Furthermore, to explore the interactions between the BDT-T and 5,8dithienylquinoxaline (DTQx) in polymers, there are some exciting reports about the BDT-T-alt-DTQx-based polymers recently. [30][31][32][33][34] For instance, Hou et al reported a polymer of PBDTDTQx-T with an alternating D-A backbone of BDT-T-alt-2,3-di(3-alkyloxyphenyl)-DTQx. 32 To further study the effect of various substituted side chains on the photovoltaic properties of these BDT-T-alt-DTQx polymers, our group recently reported two other polymers of PBDTT-TQ with an alternating D-A backbone of BDT-T-alt-6,7-difluoro-2,3-di(3-alkyloxyphenyl)-DTQx and PBDTDT(Qx-2)-T with an alternating D-A backbone of BDTT-alt-6,7-dialkyloxy-2,3-di(4-alkyloxyphenyl)-DTQx, 33,34 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…29 Furthermore, to explore the interactions between the BDT-T and 5,8dithienylquinoxaline (DTQx) in polymers, there are some exciting reports about the BDT-T-alt-DTQx-based polymers recently. [30][31][32][33][34] For instance, Hou et al reported a polymer of PBDTDTQx-T with an alternating D-A backbone of BDT-T-alt-2,3-di(3-alkyloxyphenyl)-DTQx. 32 To further study the effect of various substituted side chains on the photovoltaic properties of these BDT-T-alt-DTQx polymers, our group recently reported two other polymers of PBDTT-TQ with an alternating D-A backbone of BDT-T-alt-6,7-difluoro-2,3-di(3-alkyloxyphenyl)-DTQx and PBDTDT(Qx-2)-T with an alternating D-A backbone of BDTT-alt-6,7-dialkyloxy-2,3-di(4-alkyloxyphenyl)-DTQx, 33,34 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of M1, M2, and M3 was performed according to literature procedures [24,[31][32][33][34]. As shown in Scheme 1, PPyQxff and PPyQx were developed via Stille coupling polymerizations in moderate yields using a palladium (II) acetate/tri(o-tolyl) phosphine catalytic system.…”
Section: Resultsmentioning
confidence: 99%
“…The general synthetic route toward the polymers is outlined in Scheme . 2,7‐Bis(trimethyl‐stannyl)‐10,11‐di(3,7‐dimethyloctyloxy)dithieno[2,3‐ d :2′,3′‐ d ′]naphtho[1,2‐ b :3,4‐ b ′]dithioph‐ ene (I), DBrID, and 3,6‐bis(5‐bromo‐ thieno‐2‐yl)‐ N , N ′‐bis(2‐hexyldecyl)‐1,4‐dioxopyrrolo[3,4‐ c ]pyrrole (DBrDPP) were synthesized as the procedures reported in the references. The structures of the monomers were confirmed by 1 H NMR and elemental analyses before use.…”
Section: Resultsmentioning
confidence: 99%